IoT Security in the Banking Sector: Mitigating the Vulnerabilities of Connected Devices and Smart ATMs - Gummadi, Jaya Chandra Srikanth (Asian Business Review, 2023)
This paper examines banking IoT and innovative ATM security issues and solutions. IoT technologies improve operational efficiency and consumer interaction but can increase cyberattacks, physical tampering, and data breaches in financial systems. The research aims to identify vulnerabilities, review security measures, and provide ways to minimize banking sector-connected device hazards. The research synthesizes peer-reviewed publications, industry reports, and regulatory directives using secondary sources. The main results show that missing security standards, obsolete legacy systems, and human factors are key risks, whereas AI, ML, blockchain, and biometrics may improve Security. Physical Security and data protection rules are also stressed in the research. Policy implications include uniform security frameworks, better regulatory supervision, and ongoing security assessments. To combat increasing threats, financial institutions must work with technology suppliers and governments to create comprehensive security standards and incorporate new technologies. In conclusion, IoT adoption in banking offers excellent prospects, but strong security measures are needed to secure sensitive financial systems and retain client confidence in an increasingly linked world.
Keywords: IoT Security; Banking Sector; Smart ATMs; Connected Devices; Cybersecurity; Vulnerabilities; Risk Mitigation; Data Protection